Phytocanabinoids and synthetic cannabinoids: from recreational consumption to potential therapeutic use – a review - Teixeira, Helena M. (Frontiers in Toxicology, 2025)
Cannabinoids are part of the most popular group of illicit substances in the Western world. The word “cannabinoid” refers to any chemical substance, regardless of structure or origin, that binds to the body’s cannabinoid receptors and that has effects similar to those produced by the Cannabis plant. Regarding their origin, cannabinoids can be classified into endocannabinoids, phytocannabinoids and synthetic cannabinoids. The behavioral and physiological effects of cannabinoids have received particular attention over the last few decades, including sensations of euphoria, relaxation and loss of concentration, with their repeated use being associated with short and long-term side effects, including respiratory and cardiovascular disorders, cognitive changes, psychoses, schizophrenia and mood disorders. On the other hand, recent investigations have proposed a promising therapeutic potential of cannabinoid-based drugs for a wide range of medical situations, including neurological and psychiatric disorders, among other indications. The growing popularity in the use of cannabinoid-based compounds, both for recreational and therapeutic purposes, has been accompanied by an equally continuous and growing evolution of knowledge regarding their potential harmful and beneficial effects. However, there are several open questions and challenges to be answered, which require more and better investigations. This article’s main objectives are: i) to understand the importance of the action of cannabinoids in humans; ii) identify the different types of cannabinoids that exist and understand the differences in their action; iii) distinguish the legislative framework for cannabinoid consumption; iv) identify the possible adverse effects of cannabinoid consumption, as well as their potential benefits; v) know the existing medical-scientific evidence in terms of therapeutic potential, particularly in relation to aspects of safety and efficacy; vi) encourage critical thinking about the recreational consumption and therapeutic use of cannabinoids, based both on currently available evidence and gaps in knowledge.